Penerapan Pompa Air Tenaga Surya untuk Irigasi Sawah di Desa Pruwatan, Kabupaten Brebes, Jawa Tengah: Implementation of Solar Water Pumps for Rice Field Irrigation in Pruwatan Village, Brebes Regency, Central Java - Sudarmaji, Arief; Haryanto, Totok Agung Dwi; Lestari, Sri; Mudmainah, Siti; Febriyono, Wahyu; Murdiantoro, Randi Adzin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Water shortages during the dry season are the main problem for rice farmers in Pruwatan Village, Brebes District, Central Java. Currently, many rice fields in Pruwatan Village are rain-fed. This condition has been caused by natural disasters since 2010, which have resulted in dams breaking and landslides in irrigation canal cliffs. To meet water needs, this community service activity has built a solar-powered pump installation to raise water from the Pemali River that flows through Pruwatan Village to be channeled into the irrigation canal. The solar-powered pump uses an off-grid model (independent electricity without a PLN network connection) and without batteries. The pump used is a submersible type. The electrical energy to drive the pump comes 100% from the installed solar panels. The main device of the solar-powered pump consists of a series of 10,000 Wp solar panels, two units of 3 HP built-in inverters, two units of 3 HP submersible pumps, and a safety circuit (MCB). The pumps used are two 3 HP submersible pumps installed in parallel. The pump raises water from the Pemali River to the irrigation channel about 120 meters away with an elevation of 30 meters. The built-in inverter has a short circuit safety device, over/under voltage and undervoltage detection, and easy and user-friendly operation.